2014
DOI: 10.5194/amt-7-1803-2014
|View full text |Cite
|
Sign up to set email alerts
|

Statistical modelling of collocation uncertainty in atmospheric thermodynamic profiles

Abstract: Abstract. The quantification of measurement uncertainty of atmospheric parameters is a key factor in assessing the uncertainty of global change estimates given by numerical prediction models. One of the critical contributions to the uncertainty budget is related to the collocation mismatch in space and time among observations made at different locations. This is particularly important for vertical atmospheric profiles obtained by radiosondes or lidar.In this paper we propose a statistical modelling approach ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…Fassò et al, 2014), or based on some level of parametrization of atmospheric variability (e.g. Sofieva et al, 2014, and references therein).…”
Section: An Observing System Simulation Experimentsmentioning
confidence: 99%
“…Fassò et al, 2014), or based on some level of parametrization of atmospheric variability (e.g. Sofieva et al, 2014, and references therein).…”
Section: An Observing System Simulation Experimentsmentioning
confidence: 99%
“…Both quantities were calculated to quantify uncertainty and redundancy in the IWV time series, as well as in the times series of the vertical profile of water vapour mixing ratio. In this investigation of time series of atmospheric water vapour measurements, entropy includes all contributions affecting the uncertainty of a measurements time series -sampling uncertainty, uncertainty due to the time and vertical average, atmospheric variability, and all other relevant environmental factors (Kitchen, 1989;Fassò et al, 2014), such as solar radiation affecting daytime in situ soundings. Figure 2 (left) is an example of a series of samples of the IWV for the Lindenberg instruments (Table 1), while Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Linear correlation (Pearson's or Spearman's) has typically been used to study redundant measurements and their reliability. More recently, Fassò et al (2014) presented a new approach for an advanced statistical modelling based on functional data analysis of the relationships among collocation uncertainty and a set of environmental factors (e.g. wind speed and wind direction).…”
Section: F Madonna Et Al: Quantifying the Value Of Redundant Measurmentioning
confidence: 99%
“…Drift distances are generally larger in midlatitudes than in the tropics, are larger in winter than in summer, and vary with wind direction (Seidel et al 2011b). Fassò et al (2014) established a rigorous statistical basis for understanding the extent to which collocation uncertainty is related to environmental factors, altitude, and distance. Using simultaneous radiosonde profiles of pressure, temperature, humidity, and wind at two locations ~52 km apart, they showed that the largest contribution to the collocation uncertainty is related to airmass origin, affecting the direction in which the radiosonde moves.…”
Section: How Does Science Inform Gruan Operations and Plans?mentioning
confidence: 99%
“…Similarly, the collocation information arising from this comparison provides a valuable piece of metadata to GRUAN profiles and allows for comparisons between stations across GRUAN for each satellite. Currently, the analysis contains no specified uncertainty on the satellite measurements and also no consideration of collocation uncertainty (Fassò et al 2014). Collocation experiments based on GRUAN profiles, satellite soundings, and GNSSbased radio occultations are expected to provide further insight (WMO 2014a).…”
Section: What Observational Data Products and Services Is Gruan Provimentioning
confidence: 99%